2016
DOI: 10.1016/j.cryogenics.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the quench propagation along Nb3Sn Rutherford cables with the THELMA code. Part II: Model predictions and comparison with experimental results

Abstract: a b s t r a c tTo improve the technology of the new generation of accelerator magnets, prototypes are being manufactured and tested in several laboratories. In parallel, many numerical analyses are being carried out to predict the magnets behaviour and interpret the experimental results. This paper focuses on the quench propagation velocity, which is a crucial parameter as regards the energy dissipation along the magnet conductor. The THELMA code, originally developed for cable-in-conduit conductors for fusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…There are some aspects to consider in the analysis of the experimental estimations of v p . Ideally, it is preferable to estimate quench propagation velocities farther away from the heater, which is even more relevant in Rutherford cables, as during the first stages of quench development different velocities can be obtained from different individual strands [21] [27]. Nevertheless, in real experiments if longer distances from the heater are sensed to estimate v p , the temperature of the hot-spot may also increase considerably depending on the sheath properties, and may cause the irreversible damage of the cable.…”
Section: Quench Propagation Velocitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some aspects to consider in the analysis of the experimental estimations of v p . Ideally, it is preferable to estimate quench propagation velocities farther away from the heater, which is even more relevant in Rutherford cables, as during the first stages of quench development different velocities can be obtained from different individual strands [21] [27]. Nevertheless, in real experiments if longer distances from the heater are sensed to estimate v p , the temperature of the hot-spot may also increase considerably depending on the sheath properties, and may cause the irreversible damage of the cable.…”
Section: Quench Propagation Velocitiesmentioning
confidence: 99%
“…In the cables analysed in this study, the predictions given by Wilson and Dresner show rather good agreement with the experimental values. It is worth noting that despite of the simplifying assumptions of these models, they give valuable estimations of propagation velocities, at least as first approximations, not only for wires and tapes [23] but also for cables [27]. For example, recent studies by Manfreda et al [27] in quench propagation along Nb 3 Sn Rutherford cables concluded that predictions by Wilson's and Dresner's analytical models give close approximations, although they tend to overestimate the experimental values, mainly at lower temperatures (1.9 K), whereas at 4.2 K they give more accurate predictions, especially when using Dresner's equation.…”
Section: Quench Propagation Velocitiesmentioning
confidence: 99%
“…Several models have been used to study the quench behavior of Rutherford-type cable structures in the past. Notably, the CUDI model has been used to study their thermal stability [7,8,9] and the THELMA model was used to study quench propagation [10,11].…”
Section: Network Modelmentioning
confidence: 99%
“…During the test of the last dipole (SP 105) a high quench propagation velocity (QPV) was observed for quenches originating in the magnet's midplane, the area where the stress is larger and the magnetic field gradient is maximum. Quench propagation on Nb 3 Sn Rutherford cables has been studied and modeled before [6], [7], [8], but for configurations without a magnetic field gradient across the width of the cable. This motivated an investigation on the quench propagation of quenches in all the 11 T model magnets.…”
Section: Introductionmentioning
confidence: 99%